2020
DOI: 10.1016/j.bbi.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blueberry interventions on cognitive performance and mood: A systematic review of randomized controlled trials

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 56 publications
0
52
1
1
Order By: Relevance
“…The purpose of the present study was to evaluate the efficacy of a fruit and vegetablebased extract versus placebo on cognitive function in healthy subjects in non-acute consumption. We hypothesized that an improvement could be achieved in accordance with previous studies although they were carried out in a population with neurodegenerative diseases or the polyphenolic extract used was not composed of a mixture of phenolic compounds [11,[52][53][54][55][56]. The results obtained by other authors with different extracts followed a similar trend [46,57,58], either using melon concentrate supplementation and its influence on psychological stress and mental fatigue, using the administration of soy isoflavones in elderly men evaluating the visual-spatial memory and verbal fluency in the subjects, or in the evaluation of the efficacy of Ginkgo biloba extract in people over 55 years of age, where improvements were obtained assessing the speed of processing skills.…”
Section: Discussionmentioning
confidence: 85%
“…The purpose of the present study was to evaluate the efficacy of a fruit and vegetablebased extract versus placebo on cognitive function in healthy subjects in non-acute consumption. We hypothesized that an improvement could be achieved in accordance with previous studies although they were carried out in a population with neurodegenerative diseases or the polyphenolic extract used was not composed of a mixture of phenolic compounds [11,[52][53][54][55][56]. The results obtained by other authors with different extracts followed a similar trend [46,57,58], either using melon concentrate supplementation and its influence on psychological stress and mental fatigue, using the administration of soy isoflavones in elderly men evaluating the visual-spatial memory and verbal fluency in the subjects, or in the evaluation of the efficacy of Ginkgo biloba extract in people over 55 years of age, where improvements were obtained assessing the speed of processing skills.…”
Section: Discussionmentioning
confidence: 85%
“…A growing number of epidemiological studies support a role for polyphenols in the prevention of chronic non-communicable diseases such as cardiovascular disease (CVD) [14], cancer [15] and neurodegenerative diseases [14,16]. Furthermore, animal studies have demonstrated the ability of polyphenols to improve cognitive performance and memory [17,18] and, more recently, these results have been replicated in human studies [19,20]. Regarding mental health, a growing body of data from animal and human studies has emerged supporting the role of a variety of dietary polyphenols in affecting behaviour and mood through anxiolytic and antidepressant-like properties, mediated through multiple molecular and cellular pathways [21].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms aside, what is clear from the research todate is that cognitive benefits of blueberries are tangible, observable effects arising from small to moderate quantities of blueberries. Systematic reviews have revealed positive effects for extracts, juices, and whole berries (usually freeze-dried and powdered) at doses equivalent to 1 cup of fresh blueberries or less (Travica et al 2020;Hein et al 2019). Such quantities are easily achievable within a normal diet, and it is likely that we would all benefit from consuming them regularly, while awaiting further research on the precise cognitive domains influenced, additional benefits of longer-term supplementation, detailed mechanisms of action responsible, and the real-world relevance of the cognitive benefits attained.…”
Section: Resultsmentioning
confidence: 99%